Design and synthesis of reversible logic - Chua, Shin Cheng (Curtin University, 2016)
Energy lost during computation is an important issue for digital design. Today, all electronics devices suffer from energy lost due to the conventional logic system used. The amount of energy loss in the form of heat leads to immense challenges in nowadays circuit design. To overcome that, reversible logic has been invented. Since properties of reversible logic differ greatly than conventional logic, synthesis methods used for conventional logic cannot be used in reversible logic. In this dissertation, we proposed new synthesis algorithms and several circuit designs using reversible logic.